Expansion of Issuance Activities of Commercial Banks in the Securities Market - Musaev R. (Research Parks Publishers, 2021)
The article provides an overview of the importance of commercial banks in the issuance of securities in the securities market, the analysis of factors affecting their efficiency, ways and prospects for expansion today.